A novel method of cardiac arrhythmia detection in electrocardiogram signal. (25th August 2020) - Gupta, Varun; Mittal, Monika
Electrocardiogram (ECG) is an essential approach for observing the right condition of the heart. Generally, it represents P, Q, R, S, T and U waves. On the basis of these waves doctors can accurately diagnose cardiac arrhythmias. ECG signal is nonlinear in nature and due to this, its analysis becomes very much complex and needs extra attention. So a more reliable and accurate technique is needed for saving the life of the heart patients. Therefore, chaos theory has been applied for more accurate and reliable analysis of different ECG databases. R-peak is very crucial for classifying cardiac arrhythmia. Short time Fourier transform (STFT) and their frequency contents have been used for detecting the R-peaks. In this paper physioNet databases have been tested.